2002
DOI: 10.1063/1.1504083
|View full text |Cite
|
Sign up to set email alerts
|

A fully state- and angle-resolved study of the H+HD→D+H2 reaction: Comparison of a molecular beam experiment to ab initio quantum reaction dynamics

Abstract: We present the results of a joint experimental and theoretical investigation of the reaction dynamics of the HϩHD→DϩH 2 chemical reaction. The experiment was performed using a crossed molecular beam apparatus that employed the Rydberg-atom time-of-flight detection scheme for the product D atom. The photolysis of a HI precursor molecule produced a beam source of hot H atoms, which, when crossed with a cold HD beam, yielded two well-defined center-of-mass collision energies, E C ϭ0.498 and 1.200 eV. The resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 78 publications
5
48
0
Order By: Relevance
“…A simple picture to interpret the energy dependence of the state-to-state reaction probabilities, based on the adiabatic model, has recently been advanced by Chao et al [41] and Harich et al [35]. As illustrated by the schematic diagram in figure 12, the adiabatic potential curves correlate the initial and final rovibrational states along the reaction coordinate.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation
“…A simple picture to interpret the energy dependence of the state-to-state reaction probabilities, based on the adiabatic model, has recently been advanced by Chao et al [41] and Harich et al [35]. As illustrated by the schematic diagram in figure 12, the adiabatic potential curves correlate the initial and final rovibrational states along the reaction coordinate.…”
Section: 2mentioning
confidence: 98%
“…n 0 ;E, J ) have been observed in a number of reactions studied by using accurate quantum scattering calculations. For example, Chao et al [41] have analysed the oscillation in P R (n ! n 0 ;E, J ) vs. E for the H þ HD reaction and established the close connection to the QBS energies.…”
Section: 2mentioning
confidence: 99%
“…In addition, highly internally excited HD(ν , j ) products, particularly the HD(ν = 4, j ) manifold, exhibit a more isotropic angular distribution [9][10][11][12]. The deuterium atom Rydberg tagging technique was employed in the study of an H + HD → H 2 (ν , j ) + D hydrogen exchange variant [13,14], where the forward peak has been attributed to the well-known time-delayed mechanism observed in the H + D 2 → HD(ν = 2, 3, j = 0) + D reaction [8,[15][16][17][18][19]. Finally, Kliner et al [20] have studied the H + para-H 2 → ortho-H 2 (ν , j ) + H reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In a later report, Althorpe and coworkers analyzed the forward scattering peak using full quantum dynamics calculations based on the BKMP2 PES [45], which was claimed to have an accuracy of about 5 cm −1 , and concluded that the forward scattering peaks observed in the DCS for the H + D 2 reaction were associated with the time-delay in the transition state region [46]. [47,48]. Theoretical state-resolved differential cross section using the highly accurate BKMP2 PES are in quantitative agreement with the experimental results (see also Fig.…”
Section: The H + H 2 Reaction: Probing Quantized Bottleneck Statesmentioning
confidence: 99%